Remarks on Inachoididae Dana, 1851, with the description of a new genus and the resurrection of Stenorhynchinae Dana, 1851, and recognition of the inachid subfamily Podochelinae Neumann, 1878 (Crustacea, Decapoda, Brachyura, Majoidea) - Guinot, Danièle (Zootaxa, 2012)
A new inachoidid genus Paulita n. gen. is established for Paradasygyius tuberculatus (Lemos de Castro, 1949), from thewestern Atlantic. Paulita tuberculata (Lemos de Castro, 1949) n. comb. differs from Paradasygyius depressus (Bell,1835), from the eastern Pacific, the type species and only remaining species of Paradasygyius Garth, 1958, by a numberof characters mainly related to the carapace, thoracic sternum, abdomen, and first gonopod. Paulita n. gen. shares the di-agnostic characters of Inachoididae Dana, 1851, in particular the latero-external parts of pleurites 5–8 that extend beyondeach side of the carapace and are calcified and ornamented like the carapace, resulting in the insertion of the carapace intoa setting gutter. Stenorhynchus Lamarck, 1818, is transferred from Inachidae to Inachoididae, and the subfamily Steno-rhynchinae Dana, 1851, is resurrected. Inachoididae now consists of at least two subfamilies: Inachoidinae Dana, 1851,and Stenorhynchinae, whereas the status of Salaciinae H. Milne Edwards & Lucas, 1842, remains uncertain. The status ofseveral other American genera traditionally included in Inachidae is discussed, leading to the recognition of the followingsubfamilies besides the Inachinae emend.: Podochelinae Neumann, 1878, which is here resurrected, Anomalopodinae Stimpson, 1871, and perhaps also Eucinetopinae Števčić, 2005.